2001
DOI: 10.1111/1467-8535.00192
|View full text |Cite
|
Sign up to set email alerts
|

Children and the Internet: experiments with minimally invasive education in India

Abstract: Urban children all over the world seem to acquire computing skills without adult intervention. Indeed this form of self-instruction has produced hackerschildren who can penetrate high tech security systems. Is this kind of learning dependent only on the availability of technology? We provided slum children in New Delhi with Internet access in their settlement. The paper describes the results obtained in the first month of unsupervised and unguided access. It is observed that children seem to understand and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
87
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 9 publications
0
87
0
1
Order By: Relevance
“…Research studies (Mitra 2000(Mitra , 2003Mitra and Rana 2001;Mitra et al 2005) have found that children aged 8-14 years can learn basic computing skills on their own, irrespective of their social, cultural, religious, and intellectual background or their geographical location. These research results indicate a new learning mechanism in connected environments.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Research studies (Mitra 2000(Mitra , 2003Mitra and Rana 2001;Mitra et al 2005) have found that children aged 8-14 years can learn basic computing skills on their own, irrespective of their social, cultural, religious, and intellectual background or their geographical location. These research results indicate a new learning mechanism in connected environments.…”
mentioning
confidence: 99%
“…The pedagogy is based on minimally invasive education (MIE) (Mitra 2003;Mitra and Rana 2001), which uses the learning environment to generate an adequate level of motivation to induce learning in groups of children, without, or with minimal intervention from a teacher (Mitra et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to this, Mitra and Rana's (2001) research demonstrates that the basic functionality of most programs, such as web browsers, tend to be intuitive for most children to pick up. It is arguable therefore that teachers should be concentrating their teaching on areas such as bias and evaluation of information which are not necessarily intuitive for children and which present them with learning activities which are more likely to develop their cognitive abilities in these areas.…”
Section: Unit 6d "Using the Internet To Search Large Databases And Inmentioning
confidence: 99%
“…This is not a simple set of skills, the learning of which can easily be assessed; they are skills children may take some time to develop. As such the over-reliance on assessment may result in teachers focussing on elements which can more easily assessed, which are likely to be those more mechanical and lowerorder skills, such as the basic operation of programs, which, from the evidence of Mitra and Rana (2001) children appear to have few problems in acquiring.…”
Section: The Response Of the Rose Reviewmentioning
confidence: 99%